Technology Goes to Classroom: Learning Media Application Possibilities for Writing - Khilda Husnia Abidah (English Language Education Department, Universitas Kristen Duta Wacana (UKDW), Yogyakarta, Indonesia, 2023)
It is undeniable that teaching writing needs a lot of media as it can motivate the students in producing good writing. Moreover, nowadays, most of higher education uses technology for having the easier and more efficient in teaching and learning process. Hence, it is undeniable that the teachers should utilize some learning media applications during their teaching. However, the teacher still faces some difficulties in choosing the appropriate learning media for teaching writing which makes the learning process not run well. This article aimed to review some learning media application possibilities that finally can be used as the pedagogical implications for the teachers in choosing the appropriate media used for writing in hybrid classrooms. Furthermore, as a result, the researcher found that Schoology, Padlet, Facebook, Edmodo, and Google Classroom are the appropriate learning media applications that the teachers in the writing classroom can use. It is because those media are easy to be operated and motivate students in writing. Therefore, those can be selected by the teachers for their teaching writing.